The mindful leader: a review of leadership qualities derived from mindfulness meditation - Doornich, June Borge; Lynch, Helen Miller (Frontiers in Psychology, 2024)
Mindfulness has been practiced by global leaders and companies as an efficient way to build effective leadership. Because of its popularity, plus the lack of a comprehensive theoretical framework that explains it in a leadership context, the research literature has called for a coherent account of the qualities that is derived by those leaders that practice mindfulness. Here, we aim to answer that call, by clarifying what leadership qualities can develop from practicing mindfulness. We report on a semi-systematic literature review of extant research, covering 19 research articles published between 2000-2021, plus other relevant supporting literature from the disciplines of leadership and neuropsychology. Our proposed framework consists of three main qualities of the mindful leader: attention, awareness, and authenticity. We call them the "three pillars of mindful leaders". We also propose that mindfulness meditation must be integrated into our proposed framework, as we are convinced that leaders who hope to benefit from these qualities must integrate a regular mindfulness meditation practice into their daily leadership life.